2019
DOI: 10.1103/physrevb.99.180505
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field induced s+if pairing in Ising superconductors

Abstract: We show that an in-plane Zeeman field applied to non-centrosymmetric Ising superconductors converts singlet s-wave Cooper pairs to equal-spin triplet if pairs, leading to an enhancement of the critical transition line beyond expected from Ising spin-orbit coupling. Singlet to triplet conversion relates to a phase transformation due to spin rotation by the Zeeman field and has a geometric origin. The discussion is especially relevant, but not limited to monolayer transition metal dichalcogenides.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…As already alluded to, triplet pairing is another intriguing property that may accompany Ising superconductivity. Möckli and Khodas [31,32] suggested that the superconducting state in monolayer TMD becomes parity mixed with triplet pairing-particularly the f -wave. The mixing of singlet and triplet pairing in monolayer NbSe 2 was also confirmed by Wickramaratne et al [34] through density functional theory (DFT) calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already alluded to, triplet pairing is another intriguing property that may accompany Ising superconductivity. Möckli and Khodas [31,32] suggested that the superconducting state in monolayer TMD becomes parity mixed with triplet pairing-particularly the f -wave. The mixing of singlet and triplet pairing in monolayer NbSe 2 was also confirmed by Wickramaratne et al [34] through density functional theory (DFT) calculations.…”
Section: Discussionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t points [23,24]. Further theoretical work not only outlines a broader material pool of potential Ising superconductors but also suggests a possible realization of topological superconductivity in these systems [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. This mini-review aims at providing a progress report of atomically thin superconductors with enhanced B c2 that are mostly attributed to Ising pairing (Fig.…”
mentioning
confidence: 99%
“…伊辛超导体在过渡金属硫族化物中具有普适性, 除了MoS 2 [41,62] , Xi等人 [61] , 并得到了Lv等人 [65] 在理论上的支 持和拓展. Möckli和Khodas [66] 认为面内平行磁场将s波 转变为同位旋的f 波, 最终得到s+if非常规超导. Liu [67] , Nakamura和Yanase [68] [76,77] , YBCO [78,79] , La 2 -CuO 4+δ [80] , Pr 2 CuO 4+δ [81] 和NdBaCu 3 O 7 [82] , 以及电子掺 杂的Pr 2−x Ce x CuO 4 [83,84] 和La 2−x Ce x CuO 4 [85,86] .…”
Section: 供了便利 相比单层样品中能量最低谷在K点 多层样unclassified
“…To illustrate this, we work with two basis function examples: (i)γ(k) = sgn[γ(k)], for which γ 2 (k) → ∆ 2 so and γ 2 (k) = 1. This toy example is extensively used throughout the literature and in some situations gives qualitatively correct results [21,23,35]; (ii) γ(k) = √ 2 cos(3ϕ k ), which implements a more realistic SOC for the point group D 3h . The case (i) is frequently used for multi-pocket Fermi surfaces, while case (ii) is suitable for simply connected Fermi surfaces.…”
Section: The Structure Of Socmentioning
confidence: 99%
“…The imaginary i is the total Berry phase accumulated by the spins in the course of realignment, see Ref. [23].…”
Section: The Structure Of Socmentioning
confidence: 99%